STRATEGI KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PENDEKATAN PEMBELAJARAN MENDALAM DI SEKOLAH DASAR - Sasmita, Cici; Yantoro; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze school principals' strategies in implementing the Deep Learning approach in three Public Elementary Schools in Jambi City. Using a qualitative approach with a multiple case study design, data were collected through in-depth interviews with school principals, participant observation, and documentation studies at SDN 42/IV, SDN 64/IV, and SDN 54/IV Jambi City. The results reveal variations in the implementation strategies developed by each school. SDN 42/IV applied a structured, collaboration-based approach through the formation of a curriculum development team. SDN 64/IV developed a technology innovation strategy through the transformation of digital infrastructure and intensive teacher training. Meanwhile, SDN 54/IV emphasized the strengthening of learning communities through the establishment of a Professional Learning Community (PLC). The key findings indicate that the success of implementation is influenced by three main factors: the commitment of the principal's instructional leadership, continuous teacher capacity building, and the creation of a conducive learning environment. This study makes an important contribution to the development of an effective school leadership model for implementing Deep Learning, while also serving as a reference for policymakers in formulating contextual implementation strategies for educational innovation at the elementary school level.